The development of in vitro study of plant regeneration of Etligera Coccinea from Rhizome and Inflorescence Derived Callus - Nor Azizun Rusdi (Universiti Malaysia Sabah, 2009)
Tuhau, Etlingera coccinea (Blume) S. Sakai & Nagam, is a unique member of the Zingiberaceae family. Although it has a pungent odor, it is regarded as a delicacy by the Kadasan Dusun community in Sabah. The inner stem and its florescence are eaten and the whole plant is regarded to have importance in traditional medicine. This species grows to about 10m in high, its inflorescence grows separately from its young shoots, and appears directly from ground or either half immersed or buried in the ground. Micropropagation is a rapid propagation technique, but the biggest problem is contamination with fungi and bacteria. A wide range of microorganisms (filamentous fungi and bacteria) have been identified as major contaminants in this research. The contaminants have been introduced with explant, during surface sterilization methods in the laboratory by endophytic bacteria. Meanwhile, Fungus may also arrived with an explant, airborne or enter culture. Rhizomes and stems of Etlingera coccinea were used as explants (5-l0mm width) and were cultured in different types of plant growth regulators with different concentration (NAA, BAP, 2,4-D, TDZ and KIN) under fully light condition. Rhizomes and stems scales rinsed under running tape water for 1 hour were surface sterilized, then soaked in solutions containing ethanol (95%)(v/v) and different concentration of sodium hypochlorite (20%, 10%, 15%) (v/v). During the experiment, fungal contaminants were observed in full treatments. Determined contaminants were identified according to their morphological characteristic. There are also no callus have been induced for all treatments due to fungal contaminants.